Is Routine Intra-operative Gram Stain, Culture, and Sensitivity during an Appendectomy is Effective in Decreasing the Rate of Post-operative Infective Complications? - Fuad, Muqdad; Modher, Ahmed; Habash, Mohammed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Organisms blamed in acute appendicitis are right predictable and very susceptible to a wide range of broad-spectrum antibiotics. AIM: The aim of the study was to assess the clinical benefit of the routine intra-operative swab during an appendectomy in guiding antibiotic selection. METHODS: Four hundred and thirty patients underwent appendectomy halved into two groups, each 215. In Group 1, an intra-operative swab was routinely obtained for culture/sensitivity. The results of which were reviewed for helping direct antibiotic selection. No intra-operative swabs were obtained in Group 2. Both groups were given single-dose cefotaxime and metronidazole preoperatively intravenously at the time of induction of anesthesia. RESULTS: In swab group, 63/215 cultures (29.3%) revealed pathogens, while (70.7%) were negative or revealed isolated colonic commensals. Most cultures were negative or isolated colonic commensals. Fifty-two/63 cultures (82.54%) were sensitive to both cefotaxime and metronidazole, and only 11/63 (17.46%) reported resistant organisms to cefotaxime but not to metronidazole. Most pathogens were sensitive to empirical antibiotics. Twenty-two/215 patients (10.23%) developed infective complications, most (63.6%) had their cultures from the infected wound yielded different micro-organisms. Only 8/215 (3.72%) in the swab group needed a change in the empirical antibiotics for treating infective complications. In the non-swab group, 19/215 patients (8.83%) developed infective complications. Only 6/215 patients (2.8%) needed a change in the empirical antibiotics for treating infective complications. Collectively, only 14/430 patients (3.25%) required a change in the empirical antibiotics for treating infected wounds. CONCLUSIONS: Routine peritoneal swabs for culture/sensitivity during appendicectomy are of no clinical value. Such practice is considered a waste of laboratory resources and money. A single prophylactic dose of antibiotics has significant role in preventing surgical site infection.